2015
DOI: 10.1177/0004563215578190
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose non-fermenting AMPK related kinase/Pentraxin 3 and DNA damage axis: a gateway to cardiovascular disease in systemic lupus erythematosus among Egyptian patients

Abstract: These data highlight a novel role of sucrose non-fermenting AMPK related kinase/Pentraxin 3 axis in systemic lupus erythematosus pathogenesis. Sucrose non-fermenting AMPK related kinase/Pentraxin 3 combined role in immunometabolic signaling and DNA damage response is proposed to accelerate cardiovascular complications in systemic lupus erythematosus patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Likewise, an increase in DNA damage levels by double-stranded DNA break has been found in peripheral lymphocytes in SLE patients with high levels of anti-La/SSB and anti-RNP antibodies compared to SLE patients without these antibodies [ 68 ] suggesting a pathogenic role. A potential explanation for this damage could rely on a prooxidant/antioxidant imbalance which increases the plasma concentrations of malondialdehyde, a marker of oxidative stress, as well as by the decrease in the activity of the superoxide dismutase enzyme in these patients [ 69 ].…”
Section: Dna Damage In Slementioning
confidence: 99%
“…Likewise, an increase in DNA damage levels by double-stranded DNA break has been found in peripheral lymphocytes in SLE patients with high levels of anti-La/SSB and anti-RNP antibodies compared to SLE patients without these antibodies [ 68 ] suggesting a pathogenic role. A potential explanation for this damage could rely on a prooxidant/antioxidant imbalance which increases the plasma concentrations of malondialdehyde, a marker of oxidative stress, as well as by the decrease in the activity of the superoxide dismutase enzyme in these patients [ 69 ].…”
Section: Dna Damage In Slementioning
confidence: 99%
“…Our demonstrated AICAR effects on SNARK expression were due to NF-κB inhibition and are kinase-independent due to the lack of SNARK enzymatic activation by AICAR [ 47 ]. The observed nuclear predominance of hepatic SNARK immunoreactivity is attributed to lipotoxic, oxidative, and ER stress, which drive its nuclear translocation [ 48 ]. SNARK activates hepatic yes-associated protein (YAP)/Hippo signaling, which plays a role in how NAFLD develops into NASH [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this meta-analysis, minimizing GV is accompanied by a reduction of IMT with an estimated magnitude between 0.09 and 0.47 mm, which is consistent with an estimated 11% to 59% reduction in risk of myocardial infarction and a 13% to 70% reduction in risk of stroke [ 24 ]. Meanwhile, some studies found that IMT was associated with Phosphoinositide 3-kinase (PI3K) [ 25 ] and AMPK pathway [ 26 ], suggesting GV possibly affect IMT through PI3K or AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%